ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN TRANSFER PRICING PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2011-2014 - Rahajeng, Dhamar Anggia; Hariyanti, Widi; Suseno, Agus Endrianto (Jurnal Bisnis dan Kewirausahaan, 2019)
He purpose of this study was to examine the effect of taxes, bonus scheme, and foreign ownership in the transfer pricing decisions on manufacturing companies in Indonesia Stock Exchange in 2011-2014. Transfer pricing is defined as a special sale price that is used in exchange of interdivisional to record the revenue division division seller and buyer costs. The data used in this study is a secondary archival data. Data obtained from the manufacturing company's annual reports (2011-2014) sourced from www.idx.co.id. The hypothesis in this study were tested using binary logistic regression analysis. The population in this study were 130 companies listed on the Stock Exchange in 2011-2014. Based on purposive sampling method, samples obtained as many as 33 companies.The results of data processing can be concluded as follows: there is the influence of variable tax bonus scheme, and foreign ownership in the variable transfer pricing with the value of coefficient of determination of 18.4% which reflects the variation of tax bonus scheme, and foreign ownership in influencing the decision of transfer pricing. The tax effects and bonus scheme was also statistically significant influence transfer pricing, with a significance level of each of 0.035 and 0.046 were less than 0.05. Foreign ownership in the variable does not significantly affect the transfer pricing decisions with significant value for 0.437 is well above 0.05. The findings provide an opportunity for further research to examine the effect of any other variable of the transfer pricing decisions.